Zmiany w narządzie wzroku w przebiegu zakażenia prątkiem gruźlicy – obserwacje własne - Kępa, Beata; Grałek, Mirosława; Kanigowska, Krystyna; Chipczyńska, Barbara (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Ocular tuberculosis occurs rarely and causes many diagnostic difficulties. The aim of this paper is to provide an analysis of diagnostic problems of ocular changes as a consequence of Mycobacterium tuberculosis infection in children. Between 2006 and 2007 there were 7 children at the age 8 to 16 years old, treated in Ophthalmic Department. The infection or contact with Mycobacterium tuberculosis was diagnosed through the range of examination. Diagnosis of tuberculosis included chest radiography, computed tomography of lungs, tuberculin skin test and bronchoscopy. Gastric and bronchial aspirates were used for bacterial and genetic investigations. In eyes with ocular tuberculosis there were various intraocular changes. The most common clinical presentation occurred by intermediate uveitis, posterior uveitis and optic neuritis. 5 children were treated with antituberculous drugs, 2 children were observed without treatment. Examination and treatment of ocular tuberculosis required cooperation with specialists of pulmonary diseases.